Wireless mesh network based on sub-GHz radio - Venkataraghavan Aparajitha (2018)
The exceedingly large amounts of usage of the traditional 2.4 GHz ISM band for various applications has led to radio communications seeking an alternate frequency for operation. The sub-GHz frequency spectrum is one such band currently being tested for radio communications. This project deals with the development of a wireless mesh network in the sub-GHz frequency range to target applications that track personal mobility devices. Communication between two nodes is established, which enable collection of the received signal strength data at various distances. Further, with these measurements, the large-scale path loss and small-scale multipath fading are evaluated, leading to characterization of the wireless channel. Lastly, the results obtained from these characterizations are used to formulate some rules for the placement and distribution of wireless mesh nodes to cover a wide local area.